A condition structural index (CSI) using principal component analysis (PCA) for normal, damage and repair conditions of CFRP laminate - Mohd Aris, Khairul Dahri; Mustapha, Faizal; Salit, Mohd Sapuan; Abang Abdul Majid, Dayang Laila (2012)
The paper deals with data reduction technique by using the principle component analysis (PCA) applied to the carbon fiber reinforced plastic (CFRP) panels for structural health monitoring study. Two CFRP panels were subjected to damage and repair coincide with typical aircraft structural repair manual (SRM). Data was taken at normal/ undamaged, damaged and repaired condition by placing PZT smart sensors at predetermined distanced across the damaged and repaired structure. A time-based data response was captured for post analysis during the interrogation on the structure at each condition. The raw data was captured in a Lamb wave form and only the interested intervals were selected by using Morlet wavelet analysis to evaluate the Condition Structural Index (CI) and Amplitude Based Assessment (ABA) for each conditions. The results were evaluated by using the PCA technique in order to distinguish the characteristic of the normal, damage and repair conditions. The results showed that in all cases considered, it was possible to distinguish the conditions of normal, damaged and repaired states with promising accuracy and repeatability of the data.